Energy Poverty and Education: Empirical Evidence from Indonesia - Hilma Oktaviani; Djoni Hartono (Economics Development Analysis Journal, 2022)
Energy poverty in Indonesia has brought negative impacts on various sectors, including education which is the fourth target in the Sustainable Development Goals. This study explores how energy poverty, which is proxied by the percentage of households consuming <32.4 kwh per month in district or cities in Indonesia in 2015 and 2017, affects education, which is proxied by average years of schooling in district or cities in Indonesia in 2019. By applying the 2SLS method, the instrument variable approach used is the geographical characteristics of an area which is the mean elevation value approach in districts or cities to accurately predict the impact of energy poverty on average years of schooling. The results show a negatively significant impact on education for both energy-poor condition. The results for the first condition (2015) shows that 0.993 year of average years of schooling will be lost due to energy poverty. Whereas in the second condition (2017), 0.164 year of average years of schooling will be lost. This research also serves as an empirical evidence that energy poverty does not directly affect the average years of schooling in districts and cities in Indonesia.